The Association of Structural Inequities and Race With Out-of-Hospital Sudden Death During the COVID-19 Pandemic. (18th May 2021) - Mountantonakis, Stavros E.; Epstein, Laurence M.; Coleman, Kristie; Martinez, Johanna; Saleh, Moussa; Kvasnovsky, Charlotte; Brown, Rachel-Maria; McCulloch, Elizabeth; Kuvin, Jeffrey; Richardson, Safiya; Makker, Parth; Lesser, Martin; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Social influencers of health namely race, ethnicity, and structural inequities are known to affect the incidence of out of hospital sudden death (OHSD). We sought to examine the association between social influencers of health and the incidence of OHSD in the diverse neighborhoods of New York City during the first wave of coronavirus disease 2019 (COVID-19) epidemic. Methods: New York City ZIP stratified data on OHSD were obtained from the Fire Department of New York during the first wave of COVID-19 epidemic (March 1 to April 10, 2019) and the same period in 2020. To assess associates of OHSD, ZIP code-specific sociodemographic characteristics for 8 491 238 New York City residents were obtained via the US Census Bureau's 2018 American Community Survey and the New York Police Department's crime statistics. Results: Between March 1 and April 10, 2020, the number of OHSD rose to 4334 from 1112 compared with the year prior. Of the univariate ZIP code level variables evaluated, proportions of Black race, Hispanic/Latino ethnicity, single parent household, unemployed inhabitants, people completing less than high school education, inhabitants with no health insurance, people financially struggling or living in poverty, percent of noncitizens, and population density were associated with increased rates of OHSD within ZIP codes. In multivariable analysis, ZIP codes with higher proportions of inhabitants with less than high school education ( P <0.001) and higher proportions of Black race ( P =0.04) were independent predictors for increases in ZIP code rates of OHSD. Conclusions: Educational attainment and the proportion of Black race in New York City ZIP codes remained independent predictors of increased rates of ZIP code level OHSD during the COVID-19 outbreak even after controlling for 2019 rates. To facilitate health equity, future research should focus on characterizing the impacts of structural inequities while exploring strategies to mitigate their effects.